2017
DOI: 10.5901/mjss.2017.v8n2p317
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teaching in the Kingdom of Saudi Arabia: Past, Present and Beyond

Abstract: realized the introduction of a comprehensive English language teaching curriculum, the English Language Curriculum for Elementary, Intermediate and Secondary Schools in the Kingdom of Saudi Arabia Grades 4 -12, 2014 -2020

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…EFL teachers' lack of "enough theoretical background knowledge pertaining to the main factors that affect second-language learning, such as motivation, attitudes, aptitude, and age", their insufficient knowledge, and use of educational aids and electrical learning resources employed in English classrooms, their limited experience in material design, were also documented by several Saudi researchers (Al-Seghayer, 2016;Althobaiti, 2017;Mitchell & Alfuraih, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…EFL teachers' lack of "enough theoretical background knowledge pertaining to the main factors that affect second-language learning, such as motivation, attitudes, aptitude, and age", their insufficient knowledge, and use of educational aids and electrical learning resources employed in English classrooms, their limited experience in material design, were also documented by several Saudi researchers (Al-Seghayer, 2016;Althobaiti, 2017;Mitchell & Alfuraih, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The study of Al-Subaihy et al (2015) yielded similar results. In a more recent study conducted by Mitchell and Alfuraih (2017), it is also found that over (70%) of the EFL teachers, who completed the survey, deem themselves in need of training in testing and student feedback. In line with these results are those of Al-Harbi (2006) which revealed that EFL teachers were in need of more training in teaching methods, teaching the four language skills, teaching grammar, and utilizing teaching aids and technology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of Mitchell and Alfuraih (2017) tracked the development of English Language Education in Saudi Arabia. It emphasized that although there is a partnership between the Tatweer Company for Educational Services and the Ministry of Education, there is still a need to support improvement in the learning and teaching of English as the Kingdom continues to develop as a knowledge-based society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al-Nasser (2015) asserted that although students of public schools studied English for nine years, they could neither speak fluently nor write accurately after graduation. Mitchel and Alfuraih (2017) addressed the history of English language instruction in Saudi Arabia and applied the study to (500) teachers, teaching from 4 th to 12 th grades, out of (35,000). Results indicated that only 40% could pass the exams of English course because they neither did the assignments nor prepared the lesson despite their motivation and the teachers' utilization of modern technology.…”
Section: Statement Of the Problemmentioning
confidence: 99%